2020
DOI: 10.3389/fchem.2020.597806
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles as Smart Carriers for Enhanced Cancer Immunotherapy

Abstract: Cancer immunotherapy has emerged as a promising strategy for the treatment of many forms of cancer by stimulating body's own immune system. This therapy not only eradicates tumor cells by inducing strong anti-tumor immune response but also prevent their recurrence. The clinical cancer immunotherapy faces some insurmountable challenges including high immune-mediated toxicity, lack of effective and targeted delivery of cancer antigens to immune cells and off-target side effects. However, nanotechnology offers so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 209 publications
(245 reference statements)
0
47
0
Order By: Relevance
“…Also, by stimulating the body's immune system, cancer immunotherapy has emerged as a promising strategy for treating many types of cancer. This therapy not only eradicates tumor cells by inducing a strong anti-tumor immune response but also prevents tumor recurrence (31). The metabolism of cancer cells is usually very different from that of normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, by stimulating the body's immune system, cancer immunotherapy has emerged as a promising strategy for treating many types of cancer. This therapy not only eradicates tumor cells by inducing a strong anti-tumor immune response but also prevents tumor recurrence (31). The metabolism of cancer cells is usually very different from that of normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapeutic agents, including checkpoint inhibitors, vaccines, cytokines, and adjuvants, are commonly applied during clinical cancer immunotherapy. However, systemic delivery of immunostimulatory agents may cause potential side effects such as high immune-mediated toxicity, lack of targeted delivery, and massive degradation [ 127 ]. As is depicted in Figure 5 , BP nanomaterials can be harnessed as smart nanocarriers for loading various immunotherapeutic agents to overcome these shortcomings.…”
Section: Delivery Of Immunotherapeutic Agents For Cancer Immunotherapymentioning
confidence: 99%
“…The interactions of nanoparticles with the major immune cells, such as DCs, TAM, and T cells, are examined below. Studies on other cell types, such as B cells and natural killers, can be found in Thakur et al (2020) [ 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. Below, we introduce how nanotechnology addresses the cells of the immune system.…”
Section: Tumor Microenvironment and Nanocarriersmentioning
confidence: 99%
“…Macrophages play an important role in controlling inflammatory responses, by releasing cytokines and presenting antigens [ 125 ]. Tumor-associated macrophages (TAM) are one of the essential modulators of the tumor environment [ 126 ].…”
Section: 1 Tumor-associated Macrophages (Tam)mentioning
confidence: 99%
See 1 more Smart Citation